Analisis Penyederhanaan Rencana Pelaksanaan Pembelajaran Fisika SMA - I Made Ari Winangun (Pramana: Jurnal Hasil Penelitian, 2022)
The Lesson Plan (RPP) is a very important component as a guide for the teaching and learning process. Therefore, the designed RPP must be adaptive, applicable, and simple. This is the basis for carrying out research that aims to describe the simplification of lesson plans according to the Circular of the Minister of Education and Culture Number 14 of 2019 in physics learning in terms of structure, content, and alignment aspects. This study uses a qualitative method. The subjects of this study were public and private high school teachers in Karangasem Regency who were taken by purposive sampling as many as 5 teacher informants who had been certified at 4 schools. The data analysis technique was carried out through the study of the Lesson Plan (RPP) document of the subjects and the relevant literature review so that the results of the analysis and submission of recommendations were obtained. The results of this study indicate that: (i) most physics teachers do not simplify the lesson plans according to the Circular of the Minister of Education and Culture Number 14 of 2019; (ii) the RPP designed by all physics teachers is appropriate in terms of the depth of the material, learning techniques, and time allocation, but there are RPPs that do not show the learning mode applied, namely online or face-to-face; and (iii) most teachers are not able to adjust the learning objectives to the assessment to be carried out.